VIDEO ANIMASI STOP MOTION SEBAGAI MEDIA PEMBELAJARAN OFFLINE DALAM MODEL PEMBELAJARAN RECIPROCAL TEACHING PADA MATERI IKATAN KIMIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMA NEGERI 4 AMBON - Mathelumual, Mince; Manoppo, Yance; Manuhutu, Julita B (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2023)
This study aims to improve the learning outcomes of students using the video of the stop motion animation as an offiler learning media in the reciprocal teaching learning model on chemical bond material in SMA Negeri 4 Ambon. This research is quantitative research. The sample in this study is class X IPA-2 with the number of students as many as 30 people. This study lasted for 3 meetings on chemical ties, technique of data collection in this study included test techniques, LKS, observation using cognitive aspect sheets, observation sheet of affective aspects (attitude) and observation sheet of psychomotor aspects (skills). The Pretest is given treatment to measure students’ initial understanding while, the posttest is given to measure students’ final understanding after being given treatment. From the results of data analysis obtained showing the learning outcomes of class X IPA-2 students have achieved minimum completeness criteria (KKM), with the final value obtained is the excellent qualification of 1 student (3.3%), qualification of both 4 students (13.3%), qualification is quite 23 students (76.7%) and qualifying 2 less than 6 students (6.7%). The results of research data analysis through N-Gain calculations showed an increase in student learning outcomes obtained by 7 students (23.3%) in high categories and 23 students (76.7%) in medium category, for the average results of N-Gain scores all students obtained by 0.68 which are in medium category. From the results obtained all students meet the assessment criteria despite being in different qualifications. The results showed an increase in the use of the learning method of animation video stop motion can improve student learning outcomes.